Pre-maxillary complex morphology in bilateral cleft and hypothesis on laterality of deviated pre-maxilla - Jyotsna Murthy; Devi Manisha (Indian Journal of Plastic Surgery)
Introduction: Pre-maxillary complex (pre-maxilla [PMX] + vomer) morphology in bilateral complete cleft of primary and secondary palate (BCLCP) is very complex and less reviewed in literature. Materials and Methods: In this retrospective cross-sectional study, 200 consecutive BCLCP patients were selected. Their pre-operative clinical photographs and dental casts were evaluated by a single investigator at two different points of time, to study the morphology of PMX and vomer with special emphasis on deviation of vomer and rotation of PMX. Results: It is found that in above 70% of patients, PMX and vomer both displaced or deviated towards left side in horizontal plane and PMX rotated anticlockwise at PMX vomerine suture (PVS). In 10% of cases, both PMX and vomer are displaced towards the right side, PMX rotated clockwise at PVS. In 11% of cases, vomer is displaced towards the left side, but PMX rotated clockwise at PVS. In 5% of cases, vomer is displaced towards the right side, but PMX rotated anticlockwise at PVS. Both PMX and vomer are in midline in 4% of cases. Conclusion: Specific morphological deviation of vomer and PMX has been studied. We put forward the probable hypothesis to explain the deviation and rotation of PMX.